PENGARUH MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (K3) DAN PENERAPAN SOP TERHADAP KINERJA KARYAWAN PT PLN ( PERSERO ) UP3 BALI TIMUR - I Nyoman Yoga Aryanata; I Wayan Sukadana; I Wayan Suarjana (EMAS, 2022)
The company's role in implementing Occupational Safety and Health (OSH) Management and how employee understanding of standard operating procedure (SOP) is very necessary to support their performance so as to improve company performance. Occupational Health and Safety Management (OSH) is the company's overall management system in the context of controlling risks related to work activities in order to create a safe, efficient and productive workplace. While the notion of SOP or Standard Operating Procedure is a guide used to ensure the operational activities of an organization or company run smoothly. This study aims to analyze whether or not there is an influence of Occupational Health and Safety Management (OSH) and the application of SOP on employee performance at PT. PLN (Persero) UP3 Bali Timur. Data collection was carried out through the distribution of questionnaires and carried out on 50 employees of PT. PLN (Persero) UP3 Bali Timur. Data analysis in this study used the SPSS version 25 application. The sample was determined by the population method or the census method and data testing techniques From the results of the analysis carried out, it is obtained, 1) Occupational Health and Safety Management (OSH) has a positive and significant effect on employee performance at PT. PLN (Persero) UP3 Bali Timur. 2) The application of SOP has a positive and significant effect on employee performance at PT. PLN (Persero) UP3 Bali Timur. 3) Occupational Safety and Health Management (OSH) and SOP implementation have a positive and significant impact on employee performance at PT. PLN (Persero) UP3 Bali Timur. This means that by implementing good Occupational Safety and Health (OSH) Management and by consistent application of SOPs, it can improve employee performance and will directly improve company performance.